Unlocking the Business Model Innovation Potential on a Public Blockchain Ecosystem: A Critical Realism Approach - Ambara Purusottama; Yohanes Berenika Kadarusman (Politeknik Negeri Bandung, 2022)
This study aims to explain the phenomenon of blockchain technology in business model innovation in the public ecosystem since it offers huge potential benefits for business activities to overcome existing problems, such as data ownership, security, and accessibility. This study uses the realism perspective for understanding the phenomenon. The multiple-case study strategy presents five blockchain experts who use the value system framework to find potential for public blockchain applications. The study finds that in the public blockchain ecosystem: (i) value capture is oriented to enlarge new potential income; (ii) value creation is carried out through partnerships with other entities; (iii) value delivery is delivered through decentralized application and smart contracts; and (iv) value propositions help to solve public problems. From the findings, this study proposes three types of added value. First, low value-added, i.e., blockchain exchange data/information exchange and security; second, medium value-added, wherein technology initiates collaboration performance among entities in the public ecosystem; and finally, high value-added, i.e., a blockchain encourages new market innovation. This study focuses on the literature on blockchain and business models as well as potential future research.